2009
DOI: 10.1016/j.metabol.2009.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Brain insulin infusion does not augment the counterregulatory response to hypoglycemia or glucoprivation

Abstract: Although high dosages of insulin can cause hypoglycemia, several studies suggest that increased insulin action in the head may paradoxically protect against severe hypoglycemia by augmenting the sympathoadrenal response to hypoglycemia. We hypothesized that a direct infusion of insulin into the third ventricle and/or the mediobasal hypothalamus (MBH) would amplify the sympathoadrenal response to hypoglycemia. Nine week-old male rats had insulin (15 mU) or artificial cerebrospinal fluid (aCSF- control) infused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Roles in glucoprivic feeding have been reported for the glucose transporter GLUT2 [595], the glucose-sensing glucokinase [596,597], mu (m) opiod receptors [597e599], and the orexigenic neuropeptides NPY [597,600e602] and orexin-A [603]. Interestingly, during glucoprivation, central insulin flips from being an appetite suppressor into a further stimulant of feeding [604], even though a separate report indicates that insulin-induced phosphorylation of AKT remains intact within the brain during glucoprivation [605] (see Fig. 4).…”
Section: And Refs [277e279])mentioning
confidence: 99%
See 1 more Smart Citation
“…Roles in glucoprivic feeding have been reported for the glucose transporter GLUT2 [595], the glucose-sensing glucokinase [596,597], mu (m) opiod receptors [597e599], and the orexigenic neuropeptides NPY [597,600e602] and orexin-A [603]. Interestingly, during glucoprivation, central insulin flips from being an appetite suppressor into a further stimulant of feeding [604], even though a separate report indicates that insulin-induced phosphorylation of AKT remains intact within the brain during glucoprivation [605] (see Fig. 4).…”
Section: And Refs [277e279])mentioning
confidence: 99%
“…4). Centrally administered insulin does not appear to affect other counter-regulatory responses to glucoprivation [605]. Regarding the fourth additional regulatory effect, there is evidence that most neurons sense hormones in the extracellular fluid via receptors on the primary (solitary) cilium that protrudes, like an antenna, from these cells through their dense glycocalxy and unstirred water layer, to reach miscible liquid [606,607].…”
Section: And Refs [277e279])mentioning
confidence: 99%
“…Following surgical recovery, rats underwent a hyperinsulinemic (20 mU · kg −1 · min −1 )–hypoglycemic (∼45 mg/dL) clamp, as previously described (20). Three hours before and throughout the clamp, indinavir (IDV) (10 μg/min; Merck, Whitehouse Station, NJ; n = 9) or vehicle (artificial cerebrospinal fluid [aCSF]; n = 6) was infused into the third ventricle (−2.8 mm from the bregma; Plastics One Inc., Roanoke, VA).…”
Section: Methodsmentioning
confidence: 99%
“…Whether insulin acts centrally to influence glucose counterregulation is also uncertain. In animal studies, insulin delivered directly into the brain in very large doses has been reported to amplify counterregulatory hormone secretion ( 22 24 ) or to have no direct effect ( 25 ).…”
mentioning
confidence: 99%